A multi-faceted intervention including antenatal corticosteroids to reduce neonatal mortality associated with preterm birth: a case study from the Guatemalan Western Highlands. Issue 1 (December 2016) - Garces, Ana; McClure, Elizabeth; Figueroa, Lester; Pineda, Sayury; Hambidge, K.; Krebs, Nancy; Thorsten, Vanessa; Wallace, Dennis; Althabe, Fernando; Goldenberg, Robert
Abstract Background The Global Network for Women's and Children's Health Research undertook a cluster-randomized trial to assess the impact of a multi-faceted intervention to identify women at high-risk of preterm birth at all levels of care, to administer corticosteroids to women and refer for facility delivery compared with standard care. Of the seven sites that participated in the ACT trial, only two sites had statistically significant reductions in the neonatal mortality among the target group of <5th percentile infants, and of the two, Guatemala's improvement in neonatal mortality was by far the largest. Methods We used data available from the ACT trial as well as pretrial data in an attempt to understand why neonatal mortality may have decreased in the intervention clusters in <5th percentile infants in Chimaltenango, Guatemala. The intervention and control clusters were compared in regards to ACS use, the various types of medical care, outcomes in facility and community births and among births in various birth weight categories. Results Neonatal mortality decreased to a greater extent in the intervention compared to the control clusters in the <5th percentile infants in Guatemala during the ACT Trial. ACS use for the <5th percentile infants in the intervention clusters was 49.1 % compared to 13.8 % in the control clusters. Many measures of the quality of obstetric and neonatal care improved to a greater extent in the intervention compared to the control clusters during the trial. Births in facilities and births weighing 1500 to 2500 g had the greatest reduction in neonatal mortality. Conclusions The combination of improved care and greater ACS use may potentially account for the observed difference in neonatal mortality between the intervention and control clusters. Trial registration Clinicaltrials.gov:NCT01084096 .